Evaluating the psychometric properties of the Swedish version of the Impostor Profile scale (IPP30) - Doshi, Vini; Antens, Marijn; Daukantaitė, Daiva (Frontiers in Psychology, 2024)
The Impostor Profile scale (IPP30) is a recently developed tool designed to delve into the nuanced aspects of the Impostor Phenomenon (IP), a psychological phenomenon where individuals wrongly attribute their successes to external factors, discounting their own abilities and often feeling like frauds. This study aimed to assess the psychometric properties, including factor structure, internal consistency, and nomological validity, of the Swedish version of IPP30 (S-IPP30).In a sample of Swedish students (N = 1,010; 76.7% women; Mage = 25.65, SDage = 6.43), Exploratory and Confirmatory Factor Analyses were conducted to scrutinize S-IPP30's structure. The analyses supported a bifactor model with six specific factors and one overarching factor. However, two items in the scale displayed poor alignment with their intended subscales, adversely affecting the internal consistency of the two subscales. Consequently, a rephrasing of these items was suggested. The remaining four S-IPP30 subscales exhibited good internal consistency (Cronbach's α = .76 -.90, McDonald's ω = .77 -.91). Convergent validity was confirmed by largely replicating correlations among various S-IPP30 facets, the unidimensional IP measure, personality variables, and selfesteem, thereby accomplishing the goal of validating S-IPP30. This proposed modification of the two items requires further validation using a new sample to ensure its appropriateness and effectiveness in measuring the intended constructs.